Young Weightlifters' Performance Across Time - Byrd, R.; Baker, C.; Pierce, K.; Brady, J. (coachesinfo.com)
The purpose of this paper was to address the deficit in knowledge regarding efficacy of training for weightlifting by children. There can remain no doubt regarding whether boys and girls can participate successfully in this sport. While there was a sex difference in degree of improvement in lift total, both girls and boys made remarkable progress in competition performance. Thus, lack of efficacy, one of the old arguments against children's participation in resistive training, is laid to rest. Another, safety concerns, is receiving increasing attention and should be vigorously pursued. We wish to emphasize that results in this particular study must be viewed in light of the conservative and scientific approach to training and competition with these children. In no way do we suggest that resistive training or weightlifting are appropriate for children under any other conditions.